PREDICT FACTORS OF POPULATION GROWTH AND THE NUMBER OF POPULATION OF KARO DISTRICT USING STOCHASTIC MODEL - Ferdinand Sinuhaji, Indah Simamora (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Population growth is population transition, both growing and declining. Population growth in a region is based on birth (birth), death (death), death (in-migration) and movement out out-migration). Three factors affect population growth. One is birth, death, and displacement. Population growth in Karo District has increased annually, BPS (2002). From these details, the rising population can be classified. From the truth, examining factors driving population growth in Karo District is interesting. From these results, a stochastic model can be modelled. Population growth and population growth can be measured using birth, death and movement trends. Birth, death is a mechanism of Poisson. Population growth indicates residential land and jobs decline. A stochastic model is required to predict population growth in Karo district. This study aims to establish a stochastic growth model for the phase of birth, death and displacement trends, forecasting future demographic growth and population growth in Karo district using the assumption of making stochastic population growth models and trend data. Data is analyzed using pattern analysis and mixing processes. Karo Regency’s population growth projection results per day in 2030 are 26,2095 and population growth per day is 30,5232 in 2031. So the expected value of the Karo Regency population whose population is unknown in 2030 is 530,529 and 541,670 in 2031.